The lectionary commentary : theological exegesis for Sunday's texts - Van Harn, Roger , 1932 (Grand Rapids, Michigan : William B. Eerdmans, 2001)
Contents: v.l. The Old Testament and Acts (the first readings) -- v.2 The Acts and the Epistles (the second readings) -- v.3 The Gospels (the third readings)
Includes index
Keywords: Bible -- Homiletical use; Bible -- Criticism, interpretation, etc; Common lectionary (1992); Lectionary preaching